Advances in Diagnostic Methods for Zika Virus Infection - Herrada, Carlos A. (J Med Device, 2018)
The Zika virus (ZIKV) is one of the most infamous mosquito-borne flavivirus on recent memory due to its potential association with high mortality rates in fetuses, microcephaly and neurological impairments in neonates, and autoimmune disorders. The severity of the disease, as well as its fast spread over several continents, has urged the World Health Organization (WHO) to declare ZIKV a global health concern. In consequence, over the past couple of years, there has been a significant effort for the development of ZIKV diagnostic methods, vaccine development, and prevention strategies. This review focuses on the most recent aspects of ZIKV research which includes the outbreaks, genome structure, multiplication and propagation of the virus, and more importantly, the development of serological and molecular detection tools such as Zika IgM antibody capture enzyme-linked immunosorbent assay (Zika MAC-ELISA), plaque reduction neutralization test (PRNT), reverse transcription quantitative real-time polymerase chain reaction (qRT-PCR), reverse transcription-loop mediated isothermal amplification (RT-LAMP), localized surface plasmon resonance (LSPR) biosensors, nucleic acid sequence-based amplification (NASBA), and recombinase polymerase amplification (RPA). Additionally, we discuss the limitations of currently available diagnostic methods, the potential of newly developed sensing technologies, and also provide insight into future areas of research.